2019
DOI: 10.3329/bpj.v22i2.42298
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Malasezzia Species from Dandruff Samples and Determination of its Sensitivity Towards Antifungal Agents

Abstract: Dandruff is a perennial skin condition manifesting as inflammation and physiologic scaling on the scalp. Malassezia species are the part of the skin microflora of humans and the etiological agents of dandruff. Malassezia comprises of lipophilic and non-lipophilic yeasts. At present topical azoles are used for the treatment of dandruff. This study was conducted to isolate and identify the Malassezia spp. from dandruff samples and to determine their responsiveness towards antifungal agents such as fluconazole, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
4
0
3
Order By: Relevance
“…Blast searches revealed Neurospora intermedia, Trichoderma atroviride, and Trichosporon asahii with a percent similarity of 100.00% each. The identification test results are in line with the work of Begum et al (2019) who used a similar approach to identify dandruff causing fungi. In a study conducted by Cernansky et al ( 2020), the authors revealed that Neurospora species are often found on humans as a result of exposure to contaminated food and plants, especially sugar cane.…”
Section: Fungi Iden Fica Onsupporting
confidence: 81%
“…Blast searches revealed Neurospora intermedia, Trichoderma atroviride, and Trichosporon asahii with a percent similarity of 100.00% each. The identification test results are in line with the work of Begum et al (2019) who used a similar approach to identify dandruff causing fungi. In a study conducted by Cernansky et al ( 2020), the authors revealed that Neurospora species are often found on humans as a result of exposure to contaminated food and plants, especially sugar cane.…”
Section: Fungi Iden Fica Onsupporting
confidence: 81%
“…M. pachydermatis dalam penelitian ini mendominasi di antara spesies jamur yang lain, yaitu mencapai 50,0%. M. pachydermatis juga pernah ditemukan pada dandruff yang diperoleh dari 25 sampel mahasiswa di Bangladesh (Begum K et al, 2019). M. pachydermatis adalah flora normal pada kulit hewan peliharaan dan hewan liar (Guillot J et al, 1997).…”
Section: Prosedur Penelitianunclassified
“…However, long‐term use of the same has certain negative consequences. Some of the chemicals routinely employed in formulations have been found to cause molecular harm to cells, resulting in genetic alterations and other issues over time 5 . Furthermore, it has been discovered that the usage of these down‐the‐drain items and the release of chemicals pressurizes the freshwater environment, resulting in a detrimental ecotoxicological impact 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the chemicals routinely employed in formulations have been found to cause molecular harm to cells, resulting in genetic alterations and other issues over time. 5 Furthermore, it has been discovered that the usage of these downthe-drain items and the release of chemicals pressurizes the freshwater environment, resulting in a detrimental ecotoxicological impact. 6 Easy commercialization, reasonable price, and an ever increasing market made this a popular choice among the buyer.…”
Section: Introductionmentioning
confidence: 99%